2008
DOI: 10.4315/0362-028x-71.9.1898
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Refrigeration Practices with Emphasis on Hygiene: Analysis of a Survey and Consumer Recommendations

Abstract: A Web-enabled survey was conducted to improve knowledge of home refrigeration practices of French consumers (n = 809), with an emphasis on hygiene, and this information was used to establish recommendations. The survey targeted a convenience sample of working people. Analysis of the survey responses revealed that efforts should be directed toward improvement of microbiological control measures. Only 37% of respondents made sure the temperature in their refrigerator was 4 degrees C or below. Only 37% of respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 8 publications
1
22
1
1
Order By: Relevance
“…This is corroborated by our webenabled survey (Lagendijk et al, 2008) which showed that AFSSA staff members (n ¼ 313) neither checked the temperature of their refrigerator nor cleaned it more often than the other respondents (n ¼ 496). SOCs are colder and cleaned and disinfected more frequently (at least once a week) than DRs.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This is corroborated by our webenabled survey (Lagendijk et al, 2008) which showed that AFSSA staff members (n ¼ 313) neither checked the temperature of their refrigerator nor cleaned it more often than the other respondents (n ¼ 496). SOCs are colder and cleaned and disinfected more frequently (at least once a week) than DRs.…”
Section: Discussionsupporting
confidence: 61%
“…According to a previous study showing that AFSSA (French Food Safety Agency) staff was not significantly different from other respondents regarding hygiene practices (Lagendijk, Assere, Derens, & Carpentier, 2008), AFSSA staff members were again asked to participate to the study and 23 DRs belonging to staff members or their relatives were investigated. Six SOCs from six supermarkets in the Paris region (France) were also investigated.…”
Section: Food Refrigeration Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, absolute food safety cannot be ensured or guaranteed, no matter how good, functional, controlled and checked is the system by which food is produced (Lagendijk et al, 2008). The final, controlled segment of the food chain is the retail section, or those sections where ready-to-eat food is made available to the consumer (e.g., catering).…”
Section: Food Safetymentioning
confidence: 99%
“…. using survey data (James, Evans, & James, 2008;Lagendijk, Assere, Derens, & Carpentier, 2008). For example, pasteurized milk, which is supposed to be contaminated with 1 Bacillus cereus spore per gram, can be stored 2 days at 4°C in the factory, 2 days at 7°C at the retail and a few days in the consumer's fridge.…”
Section: Team Work Project: Determination Of the Product Shelf-life Amentioning
confidence: 99%